2017
DOI: 10.1038/s41598-017-14432-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided assessment of regional vascularity of thyroid nodules for prediction of malignancy

Abstract: Color Doppler vascular index (VI) was assessed alone and in combination with grey-scale ultrasound (GSU) in regionally subdivided thyroid nodules in diagnosing thyroid cancer. Color Doppler sonograms of 111 thyroid nodules were evaluated by a home-developed algorithm that performed “offsetting” (algorithm for changing the area of a region of interest, ROI, without distorting the ROI’s contour) and assessed peripheral, central and overall VI of thyroid nodules. Results showed that the optimum offset for dividin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…However, considering the tumoral vascularity of thyroid and nonthyroid masses, we think that these results are inconsistent [13][14][15][16][24][25][26]. In a study using a computer-aided color Doppler software, Baig et al developed a new method that divided thyroid nodule into central and peripheral regions and computed Values are given as mean values ± SD; P: significance level for all pairs the regional and entire vascular index (VI) of the nodule [9]. They found that the mean VI of malignant nodules was significantly higher than that of benign nodules, in agreement with our study [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, considering the tumoral vascularity of thyroid and nonthyroid masses, we think that these results are inconsistent [13][14][15][16][24][25][26]. In a study using a computer-aided color Doppler software, Baig et al developed a new method that divided thyroid nodule into central and peripheral regions and computed Values are given as mean values ± SD; P: significance level for all pairs the regional and entire vascular index (VI) of the nodule [9]. They found that the mean VI of malignant nodules was significantly higher than that of benign nodules, in agreement with our study [9].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using a computer-aided color Doppler software, Baig et al developed a new method that divided thyroid nodule into central and peripheral regions and computed Values are given as mean values ± SD; P: significance level for all pairs the regional and entire vascular index (VI) of the nodule [9]. They found that the mean VI of malignant nodules was significantly higher than that of benign nodules, in agreement with our study [9]. On the other hand, studies involving the characterization of thyroid nodules with CEUS in which the microvascular flow pattern is evaluated in tumoral lesions support our own findings [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Some studies have suggested that central vascularity is a feature for thyroid malignancy, whereas benign thyroid nodules tend to have peripheral vascularity ( Figure 12). 23,[35][36][37][38] However, other studies have noticed a higher association of central vascularity with benignity rather than malignant status of thyroid nodules. 31, 39,40 Shah et al 41 suggested that, when making a decision for thyroidectomy, intranodular vascularity on ultrasonography should not be used as an independent parameter to determine the risk of malignancy in patients with an atypical cytology result.…”
Section: Doppler Ultrasoundmentioning
confidence: 93%
“…46 It has been reported that using objective and quantitative measurement of nodular vascularity would allow a more accurate prediction of thyroid malignancy. 47 In a recent study, Baig et al 37 proposed a novel method that used an automated computer-aided approach for regional segmentation of thyroid nodules. The vascularity indexes of the peripheral and central sections of the thyroid nodule were evaluated to differentiate benign and malignant lesions.…”
Section: Doppler Ultrasoundmentioning
confidence: 99%